A Novel Anti-Infective Peptide BCCY-1 With Immunomodulatory Activities - Cai, Jinyang; Cui, Xianwei; Wang, Xing; You, Lianghui; Ji, Chenbo; Cao, Yan (Frontiers in Immunology, 2021)
Antibiotic resistance has been considered to be a global threat which underscores the need to develop novel anti-infective therapeutics. Modulation of innate immunity by synthetic peptides is an attractive strategy to overcome this circumstance. We recently reported that BCCY-1, a human β-casein-derived peptide displays regulatory activities on monocytes, thereby enhancing their actions in innate immune responses. However, the function of peptide BCCY-1 in host defense against infection remains unknown. In this study, we investigated the in vivo characteristics and effects of peptide BCCY-1 in mouse models of bacterial infection. Following intraperitoneal injection, the peptide BCCY-1 exhibited high level of cellular uptake by monocytes without obvious toxicities. Results revealed that peptide BCCY-1, but not the scrambled version, stimulated the chemokine production and monocyte recruitment in vivo. Treatment with BCCY-1 enhanced the pathogen clearance and protected mice against lethal infections. Because the anti-infective effects of BCCY-1 was abolished by in vivo depletion of monocytes/macrophages rather than lymphocytes and granulocytes, we conclude that monocytes/macrophages are key effector cells in BCCY-1-mediated anti-infective protection. Additionally, BCCY-1 lacks direct antimicrobial activity. To our knowledge, a human β-casein-derived peptide that counters infection by selective regulation of innate immunity has not been reported previously. These results suggest peptide BCCY-1 as a promising alternative approach and a valuable complement to current anti-infective strategy.